Green Marketing as a Tool for Building the Corporate Reputation as a Socially Responsible Organization – Critical Approach - Danuta SZWAJCA (Communications of International Proceedings, 2020)
Enterprises are trying to build their reputation as socially responsible organizations due to the growing environmental awareness of consumers and the pressure of other stakeholder groups on corporate social involvement. To this end, they use the concept and tools of green marketing. It turns out, however, that many companies only use green marketing tools to create the desired green image, not reputation. In many cases, this leads to manipulation and simulation of pro-ecological and pro-social activities, i.e. greenwashing, which is counterproductive when it comes to building a "green" reputation. The article presents the importance of green marketing in building the company's reputation as a socially responsible organization, indicating the negative effects of greenwashing practices, and proposes methods of using green marketing that give companies the chance to build the desired reputation more effectively. The research methodology was based on a critical analysis of the literature, a thematic review of research results and deductive inference.
Keywords: Green Marketing; Corporate Reputation; CSR; Greenwashing.